Análise dos fatores que influenciam o processo de interação universidade-empresa nos grupos de pesquisa da UFMA - Baêta, Aureluce Saraiva (2014)
The university-industry interactions (EU) has become the subject of increasing attention and expresses concern political, business and academic leaders, the need for the country to develop more fully its capacity for innovation. The research focused on the study of interaction in EU research groups (WG) of the Federal University of Maranhão (UFMA), having as objective to analyze and describe the main factors that influence the process of university-industry interactions in the research groups of UFMA. The interaction between university-industry-government is the key to innovation in a knowledge-based society and in this context there is a range of cultural issues, motivators, facilitators and barriers that highlight the need to investigate the issue.Thus, the question which restricted our research question arose: What are the main factors that influence the process of interaction between the GP UFMA? To answer this question we carried out a applied research, whose methodology the literature, quantitative and descriptive research; in documentary research records and documents UFMA were used. We used the cross-sectional quantitative survey method developed between March to May 2014, together with the leaders of the GP, the various knowledge areas with scope to campus of São Luis, Imperatriz, Chapadinha and Codó/UFMA. The research instrument was applied a questionnaire, using Google docs tool, having participated 55 subjects of both sexes. As a result the following information was obtained: the GP who reported having interaction with companies, and the motivating factors for interaction that had the highest levels of agreement were: having a patent, to fulfill their social role the university should transfer technology to company; bring market reality to the classroom; entering undergraduates in the research group facilitates their integration into the labor market as a researcher; access to external financing government promotes an approximation of the academy with the market. University extension;: were identified as factors facilitating the interaction process obtaining funds from companies to develop products and / or processes; students who participate in the industry focused on academic research have an easier time entering the labor market; there is greater possibility of consulting contracts when the researcher interacts with the company. As barriers to interaction, has been the lack of information channels between academia and the market and institutional procedures for relationships with business and administrative structures that promote the university-industry relationship. The profile of GP are represented by professionals with an average age of 50 years and the time during UFMA 18 years, mostly with doctorates and the beginning of the career of the researcher from entering the UFMA. Small portion of the group leaders have declared relationship with companies, not establishing consistent connections between scientific infrastructure and the productive sector. We conclude that this study achieved its goals because it was possible to identify the profile of GP UFMA, analyze and describe how the interaction used by GP and the factors involved in university-business interaction process: motivators, facilitators and barriers.